Implementation of hydram pump technology to solve clean water crisis in Kalipuro, Banyuwangi - Herawaty Magdalena Sihombing; Hendy Pambudi Nugroho; Irsyad Idzhar; Khoirul Anam; Muhamad Rifki Akmal (University of Merdeka Malang, 2024)
Bulusari Village in Banyuwangi Regency, despite its abundant water resources, faces a significant clean water crisis that adversely affects the quality of life and health of its residents. This community service program was initiated to address this crisis through the implementation of environmentally friendly hydraulic pump technology. The primary objective was to provide a sustainable solution for clean water delivery to the rural community. The project was carried out in several stages, including community socialization, elevation measurement, hydraulic pump design, preparation of tools and materials, pump assembly, trial runs, application, and ongoing evaluation and monitoring. The hydraulic pump was designed to lift water up to 150 meters by harnessing the energy from water falling from an 8-meter height. The implementation of the hydraulic pump in Bulusari Village has had a significant positive impact, resulting in increased access to clean water, improved health outcomes, and enhanced environmental awareness among villagers. The pump has consistently delivered water at a rate of 4.8 liters per minute, proving its effectiveness. Guidelines for periodic monitoring and evaluation have been established to ensure the long-term functionality of the pump. This project has successfully alleviated the clean water crisis in Bulusari Village, thereby improving the villagers' quality of life and health.